SUBCELLULAR MANIPULATION OF SUCROSE METABOLISM IN TRANSGENIC PLANTS - Sonnewald, Uwe; et al. (Journal of Experimental Botany, 1993)
Transgenic plants were regenerated and analysed. All transgenic plants showed stunted growth accompanied by reduced root formation. Starch and soluble sugars accumulated in source leaves indicating that long-distance transport of photoassimilates is dependent on sucrose. As a consequence of sugar accumulation photosynthesis is inhibited, demonstrating sink regulation of photosynthesis.
Keywords: SUCROSE METABOLISM; TRANSGENIC PLANTS; VACUOLAR TARGETING